A recent weakening of winter temperature association between Arctic and Asia - Wu, Bingyi; Li, Zhenkun; Francis, Jennifer A; Ding, Shuoyi (Environmental research letters, 2022)
Arctic warming and its association with the mid-latitudes has been a hot topic over the past two decades. Although many studies have explored these issues, it is not clear how their linkage has changed over time. The results show that winter low tropospheric temperatures in Asia experienced two phases over the past two decades. Phase I (2007/2008–2012/2013) was characterized by a warm Arctic and cold Eurasia, and phase II by a warm Arctic and warm Eurasia (2013/2014–2018/2019). A strengthened association in winter temperature between the Arctic and Asia occurred during phase I, followed by a weakened linkage during phase II. Simulation experiments forced by observed Arctic sea ice variability largely reproduce observed patterns, suggesting that Arctic sea ice loss contributes to phasic (or low-frequency) variations in winter atmosphere and makes the Arctic–Asia temperature association fluctuate over time. The weakening of the Arctic–Asia linkage post-2012/2013 was associated with amplified and expanded Arctic warming. The corresponding anomalies in sea level pressure resembled a positive-phase North Atlantic Oscillation during phase II. This study implies that the phasic warm Arctic—cold Eurasia and warm Arctic—warm Eurasia patterns would alternately happen in the context of Arctic sea ice loss, which increases the difficulty in correctly predicting Asian winter temperature.